Competing in the open market - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
A farm business advisor for the Malawi Ministry of Agriculture explains how the opening of borders to Zimbabwean egg producers has affected Malawian farmers. He encourages farmers to form groups in order to increase their competitiveness, and to reduce their reliance on imported inputs, such as chicken feeds.